The effects of virtual community towards purchase intention of luxury streetwear in Indonesia - Fadhillah, Rezzy Azizah; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract. The luxury streetwear trend in Indonesia have just became blooming lately. Along with this trend, social media has a big role to initiate the virtual community as a place to share and exchange some information about the luxury streetwear product, the event, and sometimes they are also doing transaction in it. This research intends to find out the luxury streetwear virtual community model structured in Indonesia, identify factors that influence customers purchase intention of luxury streetwear products in Indonesia, and test the effect of virtual community towards purchase intention of luxury streetwear in Indonesia. This study using semi structured interview and online survey method to collect the data, while using open coding and PLS-SEM to analyze the relationship between the variable (hedonic and utilitarian motivation, need of uniqueness, virtual community participation, brand community’s generated content, perceived interactivity, perceived brand quality, brand awareness, brand association, attitude towards luxury streetwear virtual community, brand loyalty and purchase intention). The result indicates that virtual community participation has positive influence on purchase intention in Indonesia. The finding of this research is expected to enhance both the luxury streetwear community and luxury streetwear marketers’ knowledge to maximize the luxury streetwear business.Keywords: Luxury Streetwear, Purchase Intention, SEM-PLS, Virtual Community